Comparison between herringbone and diagonal stride techniques in cross-country skiing - Andersson, E.; Pellegrini, B.; Stöggl, T.; Sandbakk, O.; Holmberg, H. C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Diagonal stride (DS) is the commonly used technique for classical uphill skiing. Herringbone (HB) is a technique that generally resembles DS in arm and leg motion but in contrast to DS, HB is used mainly on steeper inclines. For HB, skis are laterally angled and slightly edged in order to maintain ski grip and propulsive forces without gliding. The present study was aimed to compare biomechanical differences between HB and DS. METHOD: Eight male elite cross-country skiers performed DS and HB skiing on a 7.5° uphill at a velocity of 3.7 ± 0.3 m/s, equivalent to 65% of their previously measured maximal DS velocity. Pole and plantar forces (Pedar Mobile) were recorded and cycle characteristics were obtained from these data. A paired t-test was used to identify differences between DS and HB. Significance was set at a<0.05. RESULTS: Cycle rate was 46% higher and cycle length 32% shorter in HB than DS (1.30 vs. 0.89 Hz and 2.8 vs. 4.1 m; both P<0.05). In HB, skiers used a lateral ski angle of 17° in the absence of a gliding phase, whereas in DS a gliding phase of 0.42 s was used. The leg thrust durations (0.31 and 0.26 s) differed between HB and DS, respectively (P<0.05), with a similar leg swing of 0.47 s. Relative phase durations for the leg actions were: 40% thrust and 60% swing in HB and 36% gliding, 23% thrust and 42% swing for DS (both P<0.05). The peak leg force and the rate of force development (RFD) was 17% and 18% lower in HB vs. DS (both P<0.05), with a similar time to peak force (~150 ms). For the arm action, poling times (0.31 and 0.43 s) and arm swing times (0.46 and 0.70 s) differed between the HB and DS, respectively (both P<0.05), resulting in similar relative poling and arm swing phases of ~39% and ~61%. The peak pole forces were similar at ~101 N, with a 62% shorter time to peak and a 2.6 times higher RFD in HB vs. DS (both P<0.05). The pole force impulse was 39% lower in HB, with similar leg thrust force impulses between the techniques resulting in pole to leg force impulse ratios of 5% in HB and 9% in DS (P<0.05). CONCLUSION: The primary differences between HB and DS were: 1) a substantially higher cycle rate and shorter cycle length due to the absence of gliding and 2) longer absolute and relative leg thrusts. These results demonstrate that DS should be used on most uphill inclines to effectively glide and increase cycle length. Additionally, as the uphill becomes steeper, HB is likely to be more effective in order to maintain propulsion.